La parola del diritto e il verso della macchina. Per una critica della “decisione algoritmica” - Pietropaoli, Stefano (Mechane, 2025)
This paper examines the evolving relationship between humanity and machines, exploring the implications of integrating artificial intelligence into the legal domain. While humans increasingly enhance their capabilities with artificial prosthetics, machines are adopting qualities previously considered uniquely human, such as autonomy and rationality. This convergence raises critical questions about the future of law when traditional boundaries of humanity blur. The discussion highlights the limitations of artificial intelligence systems in understanding language, despite their advanced processing capabilities. Machines, while capable of generating human-like responses, lack intrinsic comprehension, reducing their outputs to statistical predictions rather than meaningful communication. In legal contexts, this raises concerns about reducing law to computational codes – transforming the codex into code – and the risks of delegating human decisions to algorithmic processes. Critiquing the notion of “algorithmic decision-making,” the paper argues that true decision-making requires human attributes like intent, context-awareness, and ethical judgment. Machines, by contrast, merely execute pre-defined rules and produce outputs without understanding or moral accountability. Ultimately, the paper advocates for embracing the imperfection of human law, emphasizing its adaptability and connection to the societal values it serves.